Neuroblastoma messenger RNA is frequently detected in bone marrow at diagnosis of localised neuroblastoma patients. (February 2016) - van Wezel, Esther M.; Decarolis, Boris; Stutterheim, Janine; Zappeij-Kannegieter, Lily; Berthold, Frank; Schumacher-Kuckelkorn, Roswitha; Simon, Thorsten; Fiocco, Marta; van Noesel, Max M.; Caron, Huib N.; van der Schoot, C. Ellen; Hero, Barbara; et al.
Abstract: Introduction: The clinical importance of the detection of neuroblastoma messenger RNA (mRNA) in bone marrow (BM) of localised neuroblastoma patients at diagnosis remains unclear. In this prospective multicentre study, BM samples of a large cohort, were studied using real-time quantitative polymerase chain reaction (qPCR). Methods: BM samples at diagnosis from 160 patients with localised neuroblastoma were prospectively collected at Dutch and German centres between 2009 and 2013. qPCR was performed using five neuroblastoma specific markers. The association with other biological factors and the prognostic impact of BM positivity and clinical response was assessed. Results: In 58 out of 160 patients neuroblastoma mRNA was detected in BM. In 47 of the 58 positive samples only one marker was found positive. BM positivity was significantly associated with MYCN amplification (p = 0.02) and deletion of chromosome 1p (p = 0.04). In total 31 patients had an event, of which only five patients had progression to stage IV. BM positivity was not associated with an unfavourable outcome. However, the detection of more than one marker was associated with an unfavourable outcome (systemic or local relapse) (event free survival 48% versus 85%; p = 0.03) in the whole cohort and in the observation group. Conclusions: BM positivity was associated with unfavourable biological factors and might represent more aggressive tumours. Patients with qPCR positive BM should not be upstaged, because of very few systemic events in the cohort. However, for patients with more than one marker positive a more careful follow-up is advisable. These results need to be verified in a very large cohort of localised patients. Highlights: Large prospective study of 160 localised neuroblastoma patients by using quantitative polymerase chain reaction (qPCR). Bone marrow (BM) qPCR positivity was associated with unfavourable biological factors. Patients with qPCR positive BM should not be upstaged to stage IV. Patients with more than one marker positive require a more careful follow-up.